2000
DOI: 10.1074/jbc.c901002199
|View full text |Cite
|
Sign up to set email alerts
|

Definition of an Amino-terminal Domain of the Human T-cell Leukemia Virus Type 1 Envelope Surface Unit That Extends the Fusogenic Range of an Ecotropic Murine Leukemia Virus

Abstract: Murine leukemia viruses (MuLV) and human T-cell leukemia viruses (HTLV) are phylogenetically highly divergent retroviruses with distinct envelope fusion properties. The MuLV envelope glycoprotein surface unit (SU) comprises a receptor-binding domain followed by a proline-rich region which modulates envelope conformational changes and fusogenicity. In contrast, the receptor-binding domain and SU organization of HTLV are undefined. Here, we describe an HTLV/MuLV envelope chimera in which the receptor-binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 29 publications
(12 reference statements)
2
51
1
Order By: Relevance
“…Functional evaluation of different SU domains, as delineated in Figure 2, allowed us to demonstrate that, paradoxically to its 'complex' genetic organization, the HTLV SU has a modular organization that is identical to that of simple retroviruses (Battini et al, 1995), with the RBD residing at the SU amino terminal (Kim et al, 2000(Kim et al, , 2004b. Furthermore, we found that this domain was sufficient for receptor binding, as measured by FACS analysis, fusion, infection and interference to infection (Kim et al, 2000(Kim et al, , 2004b, and did not require the central proline-rich region (PRR) of HTLV Env to exert these properties (Kim et al, 2000(Kim et al, , 2004b.…”
Section: Htlv-1: a Complex Deltaretrovirus With A Simple Gammaretrovimentioning
confidence: 95%
See 1 more Smart Citation
“…Functional evaluation of different SU domains, as delineated in Figure 2, allowed us to demonstrate that, paradoxically to its 'complex' genetic organization, the HTLV SU has a modular organization that is identical to that of simple retroviruses (Battini et al, 1995), with the RBD residing at the SU amino terminal (Kim et al, 2000(Kim et al, , 2004b. Furthermore, we found that this domain was sufficient for receptor binding, as measured by FACS analysis, fusion, infection and interference to infection (Kim et al, 2000(Kim et al, , 2004b, and did not require the central proline-rich region (PRR) of HTLV Env to exert these properties (Kim et al, 2000(Kim et al, , 2004b.…”
Section: Htlv-1: a Complex Deltaretrovirus With A Simple Gammaretrovimentioning
confidence: 95%
“…Notably though, alignment of the HTLV-1 SU with that of the Friend-murine leukemia virus (F-MLV) reveals highly conserved microdomains within the SU and underscores a similar general organization of the SU (Kim et al, 2000(Kim et al, , 2004a (Figure 2). Functional evaluation of different SU domains, as delineated in Figure 2, allowed us to demonstrate that, paradoxically to its 'complex' genetic organization, the HTLV SU has a modular organization that is identical to that of simple retroviruses (Battini et al, 1995), with the RBD residing at the SU amino terminal (Kim et al, 2000(Kim et al, , 2004b.…”
Section: Htlv-1: a Complex Deltaretrovirus With A Simple Gammaretrovimentioning
confidence: 96%
“…Medium containing the various soluble RBD was harvested 48 -72 h after transfection, filtered through a 0.45-m filter, and frozen at Ϫ20°C until further use. Fusion proteins harboring the HTLV-2 RBD, H RBD rFc and H RBD eGFP, were similarly produced, as previously described (17,19). Quantification of a B RBD rFc preparation, as assessed by ELISA (Zeptometrix), revealed levels of Ͼ100 ng/ml.…”
Section: Generation Of Soluble Blv Envelope Fusion Proteinsmentioning
confidence: 99%
“…Accordingly, the gag and pol genes of HTLV-1 and BLV show strong homologies, indicative of their close evolutionary relationship (16). Deltaretroviruses, including BLV, share the same modular envelope organization as gammaretroviruses, even in the variable regions of the protein surface unit (SU) (17)(18)(19), oligomerizing as a trimer (20 -22). Although the SU has been hypothesized to harbor the putative receptor-binding domain (RBD) (18,23,24), it is significant that the cellular receptor for BLV has yet to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation